Measures of State Support for the Aviation Industry and the Impact of the Coronavirus Pandemic on the Global air Transportation Market - D. Z. Nikolishvili (Мир новой экономики, 2022)
This article analyses the international air transportation market, assessing the impact of coronavirus and government support measures. Air transport is now extremely important for the successful functioning of the global economy, its further harmonious development, and the maintenance of sustainable economic growth; allows for the mobile high-speed movement of people and goods between different continents, contributing to the development of world trade and the international tourism industry. Given that sales of high-tech goods depend on a well-functioning air transport system, there is currently no alternative to air transport for the transport of perishable goods. The current trend in the development of air transportation is focused on the growth in demand for international air transportation, the annual improvement of its infrastructure and the legislative framework in this area in the world and in individual countries. Consumers prefer air transportation to another mode of transport, which is justified by the reduction in the time of delivery of goods to anywhere in the world.